Analysis of the social-epistemological dimensions of a Clinical Teaching Unit and Small Private Online Course compared to a traditional clerkship Internal Medicine. - Esther C Hamoen; Floris M van Blankenstein; Peter G M de Jong; Marlies E J Reinders (PLoS ONE)
Clinical workplace learning is often suboptimal due to the dynamics of the clinical learning environment and several challenges encountered in clinical practice. At LUMC, clinical teachers introduced a novel blended learning program that included both the introduction of a Clinical Teaching Unit (CTU) and Small Private Online Course (SPOC). This study aimed to analyze the educational content and design of our educational interventions, by categorizing and comparing the dimensions of the learning program before and after the interventions. The novel blended learning program was integrated into a clerkship internal medicine, aiming to optimize clerks' clinical workplace learning. Therefore, a traditional inpatient ward was transformed into a CTU, featuring the introduction of learning activities that promoted multidisciplinary and interprofessional learning. It included an integrated SPOC, aiming to improve clinical reasoning skills, feedback and collaboration of the clerks. The authors analyzed the clerkships' content and design, by categorizing the social-epistemological dimensions of the teaching modes offered before (traditional clerkship) and after (including CTU and SPOC) the intervention. These dimensions consisted of individual versus group (collaborative), and objectivist versus constructive learning categories. The CTU model added eleven group activities to the clinical workplace, of which nine were characterized as constructivist-group activities. It also led to more active learning of the clerks, compared to the traditional clerkship. Analysis of the SPOC revealed 344 teaching modes in total, which included 113 objectivist-individual, 205 constructive-individual and 23 constructive-group activities. Compared to a traditional clerkship, the CTU with SPOC led to more constructivist and collaborative learning and a more diverse educational program. This study illustrates a methodology to address active and collaborative learning activities in an educational program, and offers tools to evaluate and redesign one's teaching program. The methods and models described can be applied to clinical environments in other areas of medicine.